CHANGES IN PHYSICAL FITNESS DURING MENSTRUAL CYCLE IN WOMEN PRACTICING RESISTANCE EXERCISE (Fiep Bulletin - online, 2012)
This study investigated the alterations in physical fitness during menstrual cycle in women practicing resistance exercise. The sample included ten women from Gloss gym, exercising to 6 months, age 29.4 years (± 4.6), height 1.61mt (± 0.08) and cycles of 28 days. Were evaluated the three phases of the menstrual cycle, starting by Follicular (FO) (1° to 4º day), after Ovulatory (OP) (14° day) and Luteal Phases (LP) (26° to 28° day). The following measurements were performed: total body mass, body fat (%), lean mass (%), flexibility, VO2máx. and perceived exertion (EPE) testing in the 10RM leg press 45° and pulley machines. The comparison of results at different times of the cycle was performed by one way ANOVA with repeated measures and significant level of p
Keywords: Cycle menstrual; Resistance exercise; Physical fitness